Exploring the power of visual aesthetics in advertising / Wan Kalthom Yahya … [et al.] - Yahya, Wan Kalthom; Muthusamy, Geetha; Naseri, Roszi Naszariah Nasni; Affendi, Faiza Rostam (Faculty of Art and Design, 2024)
Marketing plays a crucial role in determining the success of any organisation. Businesses can achieve significant growth by implementing a strategy that prioritises the needs and preferences of their customers. A recent study has emphasised the crucial significance of visual attractiveness in attracting customer attention and involvement. A favourable aesthetic experience can enhance the user's involvement with the interface. This article seeks to examine the capacity of utilising visual aesthetics to mould brand identity, impact consumer perception, and affect behaviour in advertising campaigns. This study will use Gestalt theory principles to enable advertisers to create more impactful and captivating advertising that captures viewers' attention, facilitates information processing, and improves brand recall. The study will utilise a quantitative methodology, using data collected via a self-administered questionnaire. The data analysis will employ structural equation modelling (SEM). The study's findings will unquestionably equip advertising marketers to improve product promotion techniques and tailor advertising campaigns.